Optimizing the Potential of Mina Padi as an Edu-Ecotourism Destination Through a Digital-Based Sustainable Tourism Program in Margoluwih Village - MASYHARI, Ghulam Ali; ESTIKAH, Nur; RIZKI, Aziz; WIBOWO, Ghiyats Amri; SUKMONO, Filosa Gita (PT Batara Swastika Harati, 2024)
Margoluwih Village is a village located in Seyegan District, Sleman Regency, Yogyakarta which has 14 hamlets and has potential in the form of agriculture, culture, culinary, and tourism potential. This village is known for its agricultural tourism with a method of combining rice and fish cultivation called Mina Padi, which has been recognized by the Food and Agriculture Organization (FAO) since 2015 and has been used as a model for agricultural management in the Asia Pacific. However, since 2019, the intensity and appeal of mina padi tourism have decreased. This is due to the lack of knowledge and skills of the community in Margoluwih Village in managing the potential of mina padi tourism, as well as the lack of regeneration of mina padi tourism village managers, then the minimal use of digital technology for branding and marketing of tourist villages through social media, the absence of expansion of partnerships with other parties for the development and sustainability of tourism programs, and the absence of regeneration of mina padi tourism managers in Margoluwih Village. Based on the results of environmental observations and interviews, therefore UKM KPM UMY, the Margoluwih Village Government, and the local community collaborated to optimize the potential of rice-fish cultivation in order to strengthen the branding of rice-fish tourism by using the Sustainable Tourism method, namely developing a tourism concept that can provide long-term impacts, both on the environment, social, culture, and economy for the present and future for all local communities and tourists who visit.